2019
DOI: 10.1128/mcb.00405-18
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Recapitulation of Nonalcoholic Steatohepatitis upon Loss of Host Cell Factor 1 Function in Mouse Hepatocytes

Abstract: Host cell factor 1 (HCF-1), encoded by the ubiquitously expressed X-linked gene Hcfc1, is an epigenetic coregulator important for mouse development and cell proliferation, including during liver regeneration. We used a hepatocyte-specific inducible Hcfc1 knockout allele (called Hcfc1hepKO) to induce HCF-1 loss in hepatocytes of hemizygous Hcfc1hepKO/Y males by 4 days. In heterozygous Hcfc1hepKO/+ females, owing to random X-chromosome inactivation, upon Hcfc1hepKO allele induction, a 50/50 mix of HCF-1-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
6
12
0
Order By: Relevance
“…These results demonstrate that the role of HCF‐1, likely as a transcriptional regulator of many genes, can differ depending on the cell context. This finding of differing roles of HCF‐1 in different cell contexts complements that in the context of resting adult mouse hepatocytes where loss of HCF‐1 leads to hepatocyte malfunction (Minocha et al , ). HCF‐1 appears to have evolved to play a multitude of cell‐specific roles in the regulation of gene expression, probably principally gene transcription but also through protein stabilization as in the case of PGC1α in hepatocytes (Ruan et al , ; Minocha et al , ).…”
Section: Discussionsupporting
confidence: 69%
“…These results demonstrate that the role of HCF‐1, likely as a transcriptional regulator of many genes, can differ depending on the cell context. This finding of differing roles of HCF‐1 in different cell contexts complements that in the context of resting adult mouse hepatocytes where loss of HCF‐1 leads to hepatocyte malfunction (Minocha et al , ). HCF‐1 appears to have evolved to play a multitude of cell‐specific roles in the regulation of gene expression, probably principally gene transcription but also through protein stabilization as in the case of PGC1α in hepatocytes (Ruan et al , ; Minocha et al , ).…”
Section: Discussionsupporting
confidence: 69%
“…We performed ChIP-Seq using an antibody against the amino-terminus of HCF-1 ( Machida et al, 2009 ), and identified ~1900 peaks for HCF-1 N ( Figure 5—source data 1 ), the majority of which are promoter proximal ( Figure 5A ). These peaks occur at genes enriched in functions connected to HCF-1 ( Minocha et al, 2019 ), including the mitochondrial envelope, the cell cycle, as well as ribonucleoprotein complex biogenesis ( Figure 5B ). Known ( Figure 5C ) and de novo ( Figure 5—figure supplement 1A ) motif analysis revealed that HCF-1 N peaks are enriched in DNA sequences linked to nuclear respiratory factor (NRF)–1, as well as the Sp1/Sp2 family of transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, similar strategies in murine hepatocytes demonstrated an increase in cell proliferation. 42 These data suggest a cell type specific function for Hcfc1. Moreover, deletion of Hcfc1 in Nkx2.1+ cells contrasts with in vitro assays because knockdown in vitro causes increased NPCs, whereas cell type specific deletion causes a decrease in Nkx2.1+ cells.…”
Section: Murine Models Of Hcfc1 Functionmentioning
confidence: 84%